Optimal thresholds for ischemic penumbra predicted by computed tomography perfusion in patients with acute ischemic stroke treated with mechanical thrombectomy. (9th June 2017) - Kameda, Katsuharu; Uno, Junji; Otsuji, Ryosuke; Ren, Nice; Nagaoka, Shintaro; Maeda, Kazushi; Ikai, Yoshiaki; Gi, Hidefuku
Abstract : Background and purpose: Optimal thresholds for ischemic penumbra detected by CT perfusion (CTP) in patients with acute ischemic stroke (AIS) have not been elucidated. In this study we investigated optimal thresholds for salvageable ischemic penumbra and the risk of hemorrhagic transformation (HT). Methods: A total of 156 consecutive patients with AIS treated with mechanical thrombectomy (MT) at our hospital were enrolled. Absolute (a) and relative (r) CTP parameters including cerebral blood flow (aCBF and rCBF), cerebral blood volume (aCBV and rCBV), and mean transit time (aMTT and rMTT) were evaluated for their value in detecting ischemic penumbra in each of seven arbitrary regions of interest defined by the major supplying blood vessel. Optimal thresholds were calculated by performing receiver operating characteristic curve analysis in 47 patients who achieved Thrombolysis In Cerebral Infarction (TICI) grade 3 recanalization. The risk of HT after MT was evaluated in 101 patients who achieved TICI grade 2b–3 recanalization. Results: Absolute CTP parameters for distinguishing ischemic penumbra from ischemic core were as follows: aCBF, 27.8 mL/100 g/min (area under the curve 0.82); aCBV, 2.1 mL/100 g (0.75); and aMTT, 7.30 s (0.70). Relative CTP parameters were as follows: rCBF, 0.62 (0.81); rCBV, 0.83 (0.87); and rMTT, 1.61 (0.73). CBF was significantly lower in areas of HT than in areas of infarction (aCBF, p<0.01; rCBF, p<0.001). Conclusions: CTP may be able to predict treatable ischemic penumbra and the risk of HT after MT in patients with AIS.